Visual communication and narrative discourse in social networks: Emma Watson’s digital identity on Instagram - Martín Matas, Patricia; Gil, Íngrid (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Social networks allow us to trace a self-management of the image with a high self-referential intention. This research analyses the digital identity of the actress Emma Watson through her visual narrative on the social network Instagram. Based on an empirical and longitudinal methodology, an exploratory study is designed to analyse the attention metrics and the images published by the actress, in order to analyse the different stages of her visual discourse and find out if there is a relationship between her aesthetics and the engagement rate produced from it.